The association between driving time and unhealthy lifestyles: a cross-sectional, general population study of 386 493 UK Biobank participants. (19th September 2019) - Mackay, A; Mackay, D F; Celis-Morales, C A; Lyall, D M; Gray, S R; Sattar, N; Gill, J M R; Pell, J P; Anderson, J J
ABSTRACT: Background: Driving is a common type of sedentary behaviour; an independent risk factor for poor health. The study explores whether driving is also associated with other unhealthy lifestyle factors. Methods: In a cross-sectional study of UK Biobank participants, driving time was treated as an ordinal variable and other lifestyle factors dichotomized into low/high risk based on guidelines. The associations were explored using chi-square tests for trend and binary logistic regression. Results: Of the 386 493 participants who drove, 153 717 (39.8%) drove <1 h/day; 140 140 (36.3%) 1 h/day; 60 973 (15.8%) 2 h/day; and 31 663 (8.2%) ≥3 h/day. Following adjustment for potential confounders, driving ≥3 h/day was associated with being overweight/obese (OR = 1.74, 95% CI: 1.64–1.85), smoking (OR = 1.48, 95% CI: 1.37–1.63), insufficient sleep (1.70, 95% CI: 1.61–1.80), low fruit/vegetable intake (OR = 1.26, 95% CI: 1.18–1.35) and low physical activity (OR = 1.05, 95% CI: 1.00–1.11), with dose relationships for the first three, but was not associated with higher alcohol consumption (OR = 0.94, 95% CI: 0.87–1.02). Conclusions: Sedentary behaviour, such as driving, is known to have an independent association with adverse health outcomes. It may have additional impact mediated through its effect on other aspects of lifestyle. People with long driving times are at higher risk and might benefit from targeted interventions.